Carbosulfan Induced Renal Toxicity in Albino Mice - B. Kaliwal2*, Raghavendra L. Ksheerasagar1 and Basappa (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Carbosulfan (2,3-dihydro-2,2dimethyl-7-benzofuronyl [(dibutyl amino) thio] methyl insecticide cum -acaricide was administered orally at doses of 12, 24, 36 and 48 mg/ kg /d to albino mice for 30 days . Mice orally administered with similar volume of olive oil were served as control. Daily body weights were recorded and mice were sacrificed on day 31st. The kidney histology, estimations of biochemical contents and enzyme activities were carried out. The histologic examination of kidney of mice treated with 12 and 24 mg /kg/d carbosulfan revealed loss of normal arrangement of cortical tubules and formation of vacuoles. The histologic study of kidney of mice treated with 36 and 48 mg/ kg/d carbosulfan showed flattened tubular cells and formation of vacuoles. The glomeruli were small atrophied and loosely attached to Bowman’s capsule. Vacuoles are found prominently due to loss of glomeruli. Study on biochemical contents of the kidney showed that the levels of DNA, RNA, protein and glycogen were decreased significantly but the level of cholesterol was increased significantly with 36 and 48 mg/kg/d carbosulfan treatment to male and female mice, except in male mice the DNA, RNA and cholesterol were not changed significantly with 36 mg/kg/d carbosulfan. Treatment with 24 mg/kg/d carbosulfan caused significant decrease in the levels of protein and glycogen in female and male mice. Study on the activity of enzymes revealed that the treatment with 36 and 48 mg/kg/d carbosulfan caused significant decrease in the activity of SDH, Na+-K+ATPase, Mg++ATPase, Ca++ATPase and ACP but there was a significant increase in the activity of LDH, ASAT, ALAT, AKP in kidney of both female and male mice .The results of the present study suggest that the carbosulfan might have affected cellular metabolism , active transport of ions across cell membrane, cellular defense mechanism and elimination system in kidney and it was dose dependent . --- 1Department of Biotechnology, C.M.R.I.T, Bangalore-37, Karnataka, India; 2P.G. Department of Studies in Biotechnology and Microbiology, Karnatak University, Dharwad – 580 003, India --- Please Cite This Article As: Raghavendra L. Ksheerasagar and Basappa B. Kaliwal. 2010. Carbosulfan Induced Renal Toxicity in Albino Mice. J. Exp. Sci. 1(8):17-22.